Deux modèles récents de la parenté à l’épreuve de la noblesse française d’Ancien Régime - Elie Haddad (L'Atelier du CRH)
Two recent models of kinship put to the test of Old Regime French nobilityThis paper proposes to test two recent models of interpretation of kinship by applying them to Old Regime French Nobility. The first one is François Héran’s model, whose diagrams of kinship are used on a complex system of kinship, which allows to show the limits of his structural approach. The second one is Gérard Delille’s interpretation of the European system of kinship between the 14th and the 17th century. It allows to underline that descent is fundamentally bilateral at this time, and thus to reveal the bias introduced by an approach founded on patrilignages.